The influence of corporate governance structure on sustainability reporting in Malaysia - Jamil, Amira; Mohd Ghazali, Nazli Anum; Puat Nelson, Sherliza (Emerald Publishing Limited, 2020)
Purpose – Following the introduction of the revised Malaysian Code on Corporate Governance in 2012 (MCCG 2012), this study aims to investigate the influence of corporate governance structure on the quality of sustainability reporting from the perspectives of agency theory and resource dependence theory. Design/methodology/approach – Based on an analysis of 126 firms’ annual reports for the year ended 2010 and 2014, this study analyses sustainability reporting quality before the introduction of MCCG, 2012 (year ended 2010) and after (year ended 2014). Findings – The findings of the study show that there was a significant increase in the quality of sustainability reporting from 2010 to 2014. Results from multiple regression analyses indicate that the number of sustainability-related training attended by the board of directors and the percentage of directors with sustainability-related experience have a significant impact on the quality of sustainability reporting. Practical implications – Observations from the study provide useful insights into the importance of the appointment of directors with sustainability-related experience as part of the criteria for directors’ appointment. Moreover, the board of directors is encouraged to attend sustainability-related training to help firms improve sustainability practices and reporting. Social implications – The increase in the quality of sustainability reporting indicates that companies are committed in ensuring that environmental degradation is put at the minimum level if not eliminated. It appears that companies are embracing the concept of sustainability reporting, and hence, contributing to improving and enhancing social well-being. Originality/value – This study contributes to the discussion of both internal mechanisms (board independence and board capital) and external mechanisms (compliance to the code on corporate governance) of corporate governance structure on the quality of sustainability reporting. The findings can be used to identify necessary mechanisms that should be enhanced to strengthen the practice of sustainability reporting.